(untitled) (Bangladesh Rice Journal, 2026)
To increase crop yield and improve cropping intensity, several key cropping systems have been practiced in Bangladesh. Nevertheless, greenhouse gas (GHG) emissions from various crops and agricultural fields have primarily been published on a country-by-country basis. In this study, Cool Farm Tool Version 2.0 beta-3 software was used to estimate total GHG emitted from selected rice crops and rice-based cropping patterns. Short-duration rice cultivars exhibited lower methane (CH4) emissions and higher grain yields than long-duration rice cultivars during both the Boro and Aman rice seasons. Among rice cultivars of the T. Aman season, BRRI dhan62, BRRI dhan66, BRRI dhan71, and BRRI dhan75 were relatively more suitable to reduce about 15-25% of CH4 emission, GHG intensity, emission factor of CH4, and subsequent GWP (global warming potential) compared to BRRI dhan49. Short-duration Boro rice cultivars like BRRI dhan28, 58, 68,74 reduced about 8-15% of CH4 emissions compared to long-duration rice cultivars (BRRI dhan29). Spatial variations in rice equivalent yield with a higher amount of net carbon stock were found in Rice-Potato-Rice and Rice-Mustard-Rice cropping patterns in the studied area, Kotiadi and Pakundia, Kishoreganj, Bangladesh. Rice-Mustard-Rice cropping pattern gave a higher net carbon balance and reduced half of the P, K, S, and Zn fertilizers in subsequent Boro season rice cultivation. Additional multi-location/years research trials with recommended cropping pattern and management via GHG measurement are necessary to validate and propose appropriate mitigation measures to reduce GHG emissions and reduce chemical fertilizer use in Bangladesh. Bangladesh Rice J.28(2): 71-79, 2024